Continuum damage mechanics models and their applications to composite components of aero-engines - Yu, Tianhong (2016)
Built on top of a consistent continuum damage mechanics (CDM) damage representation formulation, a novel damage evolution law based on the concept of damage driving force is proposed for modelling the evolution of matrix damage in UD composites. This damage evolution law has the advantage of allowing different damage evolution constants to be associated with different loading modes (corresponding to the fracture modes in Fracture Mechanics) when dealing with mixed-mode loading conditions, which avoids the unrealistic assumption in many existing theories that different loading modes make the same contribution to damage evolution. A new CDM model for UD composites is developed incorporating this damage evolution law. Thanks to the laminate test cases designed and conducted in this project, it is found that the damage initiation and propagation related material constants can be determined using these tests. These damage-related material constants served as inputs to the UD composite CDM model. Apart from the tests on laminates, detailed experimental investigation was carried out regarding damage in two types of layer-to-layer interlock 3D woven composites which are reinforced by IM7 carbon fibre (CF) and E-glass fibre (GF), respectively. The experimental data obtained and the damage processes recorded for these 3D woven composites can serve as a good reference for future interest in this area, since currently only limited studies are available in the literature regarding damage in this type of 3D woven composites. The new UD composite CDM model is applied to predict intra-laminar damage in laminates and intra-tow damage in the 3D woven composites. Compared to the experimental results, it is found that the model produced satisfactory predictions but lacking the capability to predict a severe stress-strain nonlinearity caused by shear. A new pragmatic continuum damage model is developed to capture the damage effect of inter-tow cracks in the 3D woven composites caused by warp direction tensile loading. This model works in conjunction with the intra-tow damage predicted by the aforementioned UD composite CDM model. With the successful development of these damage models, a novel damage modelling methodology for textile composites is made possible and implemented in conjunction with the UnitCells© composite characterisation tool and the artificial neural network tool developed. Through the artificial neural network for data interpolation, the constitutive behaviour of textile composite incorporating the effect of damage can be interpolated for any load combination, which is then readily available for engineering applications.